Calidad de vida y autovaloración en Estudiantes de la Universidad Nacional de Educación, 2019 - Padilla Domínguez, Ángel Andrés (2019)
The present investigation research probes the Quality of Human Life its relation with the Self-Assessment of the Physical State in university students. The aim was to research the variables through surveys and identify the importance of physical activity in the well-being of students. The quality of life constitutes the intrinsic tendency of persuasions of the current state of health, about the individual’s ability to achieve and maintain a complete level of functioning. Self-assessment is considered to be integral quality that a person has towards himself, whether positive or negative attitude. The population was made up of 100 students from Nacional University of Education, between 26 male and 74 female, with an average of 20, 78 ± 3.52 years. The research is presented in an analytical - descriptive type, with a qualitative, cross-sectional nature, using the survey for application, the Displacement Questionnaire in universities students with high standars of Life and Physical Condition as a research technique, then the statistical analysis is the result obtained for those who have an acceptable quality of life and physical condition.